Memahami Pelaksanaan Kode Etik Jurnalistik Pada Media Online (Studi Etnografi Pada Kantor Redaksi Portal Berita Online jateng.tribunnews.com) - Rahayu, Kusnurul; Manalu, S. Rouli (Interaksi Online, 2018)
This research originated from the increasing number of press violations especially related to violations of the journalistic code of ethics. As many as 30% of violations of the code of ethics are carried out by online media. The Press Council said the number of complaints related to the press throughout 2012 reached more than 500 cases and out of that number 98 cases were related to online media. As many as 76% of the complaints relate to the issue of violating the journalistic code of ethics. Therefore this study wants to know the application of journalistic code of ethics in the news production process in online media and also to find out how routine media influence the implementation of journalistic code of ethics in online media.This study uses the Hierarchy of Influence Theory, Media Ethical Theory, New Media Theory and Journalistic Code of Ethics from several existing press organizations. This research is a study that uses the constructivism paradigm using an ethnographic communication approach. The data analysis of this study is divided into three stages: description, analysis and interpretation. The research began on April 10th to May 31st, 2018 at the Tribun Jateng Online editorial for 7 weeks. The researcher looked at how the news are being processed started from the search for ideas of coverage to the news distribution stage to the public.The results of this study were obtained from observations made during the research in the field. Based on this data, it is seen how the concepts related to the journalistic code of ethics with the actual conditions in the field. The results of this study show that all parties ranging from editors in chief, journalists to editors are involved in maintaining the quality of news related to the application of the journalistic code of ethics. There are several factors that lead to violations of the journalistic code of ethics both from internal factors and external factors. This study found five important points that influence the content of the news related to the application of journalistic code of ethics, namely media routines, journalists' personal closeness, adaptation and copying acts, provision of facilities and up to the editor's role in processing the final report from journalists. Tribun Jateng Online itself has not been maximized in applying the journalistic code of ethics on every news that has been published.